2017
DOI: 10.1002/ejoc.201701021
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of Phenylpropanoids and Coumarins: Total Synthesis of Osthol

Abstract: Herein we describe a one‐pot microwave‐assisted method for the synthesis of cinnamic acid and coumarin derivatives. The synthesis begins with an aldehyde synthon, and the chosen reaction conditions determine whether a cinnamic acid or coumarin derivative is formed. A regioselective Claisen rearrangement was also efficiently incorporated into the synthetic sequence to further increase the complexity of the product. Notably, this approach provides high product yields and selectivities without the need of a pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…After the optimization of the experimental parameters and the development of a general synthetic methodology for the synthesis of different substitute coumarin derivatives (Scheme 12a), the method was further developed to incorporate a Claisen rearrangement step. In order to demonstrate the synthetic utility and versatility of the developed method, the research team performed the total synthesis of two coumarins, one of which being osthole, a natural coumarin derivative already mentioned in the anti-inflammatory paragraph (Scheme 12b) [327]. A broad range of indolo [2,3-c] coumarins have been obtained in good yields (46-88%) by Gu and co-workers in 2019 under microwave-assisted base-free intramolecular cross dehydrogenative coupling using palladium catalyst.…”
Section: Microwave Assisted Reactionsmentioning
confidence: 99%
“…After the optimization of the experimental parameters and the development of a general synthetic methodology for the synthesis of different substitute coumarin derivatives (Scheme 12a), the method was further developed to incorporate a Claisen rearrangement step. In order to demonstrate the synthetic utility and versatility of the developed method, the research team performed the total synthesis of two coumarins, one of which being osthole, a natural coumarin derivative already mentioned in the anti-inflammatory paragraph (Scheme 12b) [327]. A broad range of indolo [2,3-c] coumarins have been obtained in good yields (46-88%) by Gu and co-workers in 2019 under microwave-assisted base-free intramolecular cross dehydrogenative coupling using palladium catalyst.…”
Section: Microwave Assisted Reactionsmentioning
confidence: 99%
“…All microwave irradiation experiments were conducted at 250°C, because we and others have previously shown that the Claisen rearrangement remains incomplete at lower temperatures. In a first experiment (Table , entry 1), we tested toluene as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Along these lines, straightforward syntheses of pyranocoumarins , prenylcoumarins , furanocoumarins , chroman‐4‐ones , and chromene‐4‐ones were developed and implemented in the total synthesis of several natural products. In the above‐mentioned examples, the cyclization step proceeds through a nucleophilic acyl substitution (for the synthesis of coumarins) or through an addition across an electronically biased C─C‐multiple bond (for the synthesis of chroman‐4‐ones and chromene‐4‐ones).…”
Section: Introductionmentioning
confidence: 99%
“…Upon workup, compound 15 was isolated in a low yield of 28 % (Table , Entry 5). We were confident that our preferred reaction temperature of 250 °C could not be substantially lowered, because both our research group and that of Pospíšil recently found that E/Z isomerization of the intermediate cinnamates, a prerequesite for the cyclization into coumarin, does not efficiently proceed at temperatures lower than 200 °C. There is literature precedent for the conversion of preformed cinnamates into coumarins through an E/Z isomerization/cyclization sequence at temperatures below 100 °C, but this method requires the presence of air‐sensitive trialkylphosphines as catalysts .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, we have contributed to the field of microwave‐promoted tandem reactions with the development of a Claisen rearrangement/oxa‐Michael cyclization reaction sequence for the synthesis of substituted chromones and chroman‐4‐ones . Various 8‐allyl‐ and prenyl‐substituted coumarins have been obtained by us and others through a tandem sequence that involves a Claisen rearrangement of allyl phenyl ethers, a Wittig olefination, E/Z isomerization, and cyclization reactions. During a latter study, we also investigated an example of a tandem propargyl Claisen rearrangement/Wittig olefination reaction sequence (Scheme ).…”
Section: Introductionmentioning
confidence: 99%